DETERMINANTS OF TRADER REVENUE IN TRADITIONAL MARKETS: THE ROLE OF CAPITAL AND WORKING HOURS - Hikmahwati; Raudatul Jannah; Putriana Salman (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the dynamics of small businesses by measuring the contribution of capital and working hours to the income of traders at Sudimampir Market in Banjarmasin. Small businesses, particularly those in the informal sector, such as traditional markets, play a crucial role in the local economy, but often face various resource constraints. This study uses a quantitative approach with multiple linear regression analysis. Data was collected through questionnaires administered to merchants active at Sudimampir Market. The results indicate that the capital variable does not significantly influence merchant income (significance value 0.725 > 0.05), while working hours have a significant influence (significance value 0.003 < 0.05). These findings reflect that, in the context of small businesses in traditional markets, business success is more determined by the amount of time merchants invest in selling than by the size of their capital. Working hours are a form of time investment that directly contributes to increased income.